Coordinated existence of multiple gangliosides is required for cartilage metabolism. Issue 2 (February 2019) - Momma, D.; Onodera, T.; Homan, K.; Matsubara, S.; Sasazawa, F.; Furukawa, J.; Matsuoka, M.; Yamashita, T.; Iwasaki, N.
Summary: Objective: Gangliosides, ubiquitously existing membrane components that modulate transmembrane signaling and mediate cell-to-cell and cell-to-matrix interactions, are key molecules of inflammatory and neurological disorders. However, the functions of gangliosides in the cartilage degradation process remain unclear. We investigated the functional role of gangliosides in cartilage metabolism related to osteoarthritis (OA) pathogenesis. Design: We generated knockout (KO) mice by targeting the β1, 4-N-acetylgalactosaminyltransferase ( GalNAcT ) gene, which encodes an enzyme of major gangliosides synthesis, and the GD3 synthase ( GD3S ) gene, which encodes an enzyme of partial gangliosides synthesis. In vivo OA and in vitro cartilage degradation models were used to evaluate the effect of gangliosides on the cartilage degradation process. Results: The GalNAcT and GD3S KO mice developed and grew normally; nevertheless, OA changes in these mice were enhanced with aging. The GalNAcT KO mice showed significantly enhanced OA progression compared to GD3S mice in vivo . Both GalNAcT and GD3S KO mice showed severe IL-1α–induced cartilage degradation ex vivo . Phosphorylation of MAPKs was enhanced in both GalNAcT and GD3S KOs after IL-1α stimulation. Gangliosides modulated by GalNAcT or GD3S rescued an increase of MMP-13 induced by IL-1α in mice lacking GalNAcT or GD3S after exogenous replenishment in vitro . Conclusion: These data show that the deletion of gangliosides in mice enhanced OA development. Moreover, the gangliosides modulated by GalNAcT are important for cartilage metabolism, suggesting that GalNAcT is a potential target molecule for the development of novel OA treatments.